Patients at risk of nontuberculous mycobacterial pulmonary disease who need testing evaluated using a modified Delphi process by European experts - Loebinger, Michael R.; Aliberti, Stefano; Haworth, Charles; Jankovic Makek, Mateja; Lange, Christoph; Lorent, Natalie; Papavasileiou, Apostolos; Polverino, Eva; Rohde, Gernot; Veziris, Nicolas; Wagner, Dirk; van Ingen, Jakko (ERJ open research, 2024)
Identifying patients at risk of nontuberculous mycobacterial pulmonary disease (NTM-PD) is challenging. Delays in NTM-PD identification and management are associated with declining lung function and increased morbidity and mortality. European NTM-PD experts (n=12) participated in a three-round modified Delphi process to score symptoms and comorbidities potentially associated with NTM-PD as reasons to test for nontuberculous mycobacteria. Experts reached a consensus on the symptoms and comorbidities that should and should not prompt testing for nontuberculous mycobacteria. Requirements for testing were scored as high (mean ≥7), medium (mean ≥4-<7) or low (mean <4). Nontuberculous mycobacteria testing should be undertaken when multiple suggestive symptoms are present simultaneously in all patients except those with cancer (7.3-8.8), or when radiology is indicative of NTM-PD (≥8.9). Symptoms of persistent sputum production, recurrent respiratory infection and haemoptysis should prompt testing for nontuberculous mycobacteria, particularly in those with underlying respiratory diseases. Symptomatic patients with bronchiectasis or previous tuberculosis/NTM-PD or those being prescribed or undergoing long-term macrolide therapy for a respiratory condition should also be tested. Testing is not warranted in patients without an underlying respiratory disorder or in those without a history of respiratory disorders unless presenting with multiple symptoms. Assessing patients' risk of NTM-PD is challenging. This Delphi consensus process provides insight into symptoms and clinical characteristics that should prompt NTM-PD assessment. Timely testing and diagnosis would enable initiation of appropriate management.